RAPID HPLC PURIFICATION OF THE PHARMACOLOGICALLY ACTIVE AQUEOUS EXTRACT OF THE AERIAL PARTS OF BACCHARIS TRIMERA (LESS) DC - Collantes Díaz, Ingrit (2023)
Baccharis trimera is a plant traditionally used throughout the South America. The most common use is by infusion, that is why the same method was applied to obtain the aqueous extract from the aerial parts of the plant. The aqueous extract thus obtained was freeze-dried and subjected to analytical and semi-preparative HPLC, the latter with the purpose of isolating and identifying the maximum number of chemical components in 30 minutes. A total of 13 compounds were identified in 9 fractions (F2-F10) and the identification was performed by analysis of their NMR-1H, NMR-13C spectra and the mass spectrum by liquid chromatography coupled to mass spectrometer. The secondary metabolites identified were: 5-O-caffeoylquinic acid (F2), the mixture of 4-O-caffeoylquinic acid (F3-1), vicenin 2 (F3-2) and isocarlinoside (F3-3), the mixture of shaftoside (F4-1) and isoshaftoside (F4-2), 3,5-O-dicaffeoylshikimic acid (F5), 1,5-O- dicaffeoylquinic acid (F6), 3,5-O-dicaffeoylquinic acid (F7), the mixture of guadichanolide B (F8-1), epimer of guadichanolide B (F8-2), 7α-hydroxy-ent-clerode-3-en-15,18-diacid-16,19-dilactone (F9) and eupatorin (F10).